Is internet use unhealthy? A cross-sectional study of adolescent internet overuse (Swiss Medical Weekly, 2014)
OBJECTIVE: To assess whether problematic internet use is associated with somatic complaints and whether this association remains when checking for internet activity among a random sample of adolescents living in the canton of Vaud, Switzerland. METHODS: Cross-sectional survey of 3,067 8th graders (50.3% females) divided into average (n = 2,708) and problematic (n = 359) Internet users and compared for somatic complaints (backache, overweight, headaches, musculoskeletal pain, sleep problems and sight problems) controlling for sociodemographic and internet-related variables. Logistic regressions were performed for each complaint and for all of them simultaneously controlling variables significant at the bivariate level. RESULTS: At the multivariate level, when taken separately, problematic internet users were more likely to have a chronic condition (adjusted odds ratio [aOR] with 95% CI: 1.58 [1.11:2.23]) and to report back pain (aOR: 1.46 [1.04:2.05]), overweight (aOR: 1.74 [1.03:2.93]), musculoskeletal pain (aOR: 1.36 [1.00:1.84]) and sleep problems (aOR: 2.16 [1.62:2.88]). When considered in the full model, only sleep problems remained significant (aOR: 2.03 [1.50:2.74]). CONCLUSIONS: Our results confirm that problematic internet users report health problems more frequently, with lack of sleep being the most strongly associated and seeming to act as mediator regarding the other ones. Clinicians should remember to screen for excessive internet use their patients complaining of sleep-related problems, back or musculoskeletal pain or overweight. Clinicians should advise parents to limit the amount of time their adolescent children can spend online for leisure activities. Furthermore, limiting the number of devices used to connect to the internet could help warrant enough sleeping time.